HUBUNGAN LABA BERSIH DAN ARUS KAS OPERASI TERHADAP DIVIDEN KAS PADA PERUSAHAAN PERDAGANGAN BESAR BARANG PRODUKSI DI BEJ PADA PERIODE 1999-2002 - Hermi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2004)
Funds are important resources for an enterprise. Selling stocks is one way to collect funds from investors. Investors buy stocks and may get dividends. A company needs funds to operate the activities. According to this, company often has problems about how to obtain funds, how.to use them, and how to give it back with a proper rate of return. For investors, dividend distribution is important thing as well as company's growth. Investors need to know the result of the net income and the dividend proportion that distributed to them because they have invested their funds to the company. According to management functions, the purpose of dividend distribution is to maximize stockholder's wealth.The objective of this research is to determine the relationship between net income and operating cash flows with cash dividends. This research uses data of wholesale durable goods company listed in BEJ for period 1999 — 2002. Net income and operating cash flows are independence variables, cash dividends is dependence variables. This research uses descriptive statistics analysis, Pearson's Correlation.The result is a positive significant relationship between net income and oper-ating cash flows with cash dividends. Significant relationship means that the value of cash dividends is influenced significantly by the value of net income and operating cash flows. Positive relationship happens when the value of independent variables which are net income and operating cash flows increase, in that result the increase of the value of dependent variable that is cash dividends and vice versa.From the result, the writer gives some suggestions. In distributing cash divi-dends, the company has to concern for amount of the net income. If there is insufficient cash, the company may distribute the other form of dividends, such as stock dividends.Keywords: Net Income, Operating Cash Flow, Cash Dividend